Ethics, equity, and regulation - Tinker, Tony; Merino, Barbara Dubis; Neimark, Marilyn Kleinberg (Advances in public interest accounting, 2010)
The aims of Advances in Public Interest Accounting are twofold. Firstly, to provide a forum for researchers concerned with critically appraising and significantly transforming conventional accounting theory, practice, teaching and research. And secondly, to increase the social self-awareness of accounting practitioners, educators, and researchers, encouraging them to assume a greater responsibility for the profession's social role. Additional coverage in each volume includes: recognizing and examining the influences of gender and feminist theory, class and race on accounting practice, education, and research; expanding accounting's focus beyond the behavior of individual corporate entities; encompassing the conflicts of interest within the accounting-regulatory process and effected groups; examining accounting's participation in multinational expansion, consolidations, and changing economies undergoing transformations, such as Eastern and Central Europe and the Former Soviet Union, and the European Community.